Proportional Integral Controller of Deisobutanizer Distillation Column by Co-simulate of Aspen Plus Dynamics and Matlab Simulink - Azizah, Zahrotul (Jurnal IPTEK, 2022)
One of the control problems that is a challenge for an engineer and the chemical industry itself is chemical processes which are closely related to nonlinear processes. The linear method is the choice for many researchers to overcome problems in nonlinear processes, namely the linearization technique. This causes uncertainty whether the controller is able to work on the actual nonlinear process. The purpose of this study is to integrate Aspen Plus Dynamics and Matlab Simulink to eliminate linearization in order to be able to control nonlinear processes optimally. The method used is to perform steady state and continued dynamics simulation in the case study of the deisobutanizer distillation. Then integration of Aspen Plus Dynamics with Matlab Simulink using AMSimulink. The results show that steady-state and dynamics simulations have been successfully carried out. Aspen Plus Dynamics and Matlab Simulink are integrated and able to run together. The controllers used include reflux drum level control, top column pressure control, and reboiler level control. The response results obtained in the co-simulation run well, the process response can perform setpoint tracking.